Exploring the effects of climatic and environmental heterogeneity on the spatial activity of Patagonian bats - Giménez, Analía Laura (2025)
Background: The Patagonian region hosts endemic bat species and represents the southernmost distribution limit for several vespertilionids and molossids species. In cold temperate regions, insectivorous bats are more active during summer. However, during this period, the activity of bats can also vary spatially, depending on climatic and environmental factors (e.g., temperature, humidity, vegetation cover, productivity, elevation, proximity to water). The objective of this study was to analyze how the spatial activity of phonic groups is affected by climatic and environmental variables in a large, heterogeneous area of Patagonia, Argentina, using bioacoustic methods. Acoustic monitoring was conducted during the austral summer of 2020, at 100 points located at ten sites, in three ecoregions of Chubut Province (Patagonian Forest, Patagonian Steppe and Low Monte). Bat passes were classified into four phonic groups (PGs), each representing species with similar echolocation call structures. This classification was based on foraging habits and bioacoustic characteristics of species commonly recorded in the study area (PG1 = Myotis chiloensis, M. levis; PG2 = Lasiurus varius, L. villosissimus, Histiotus magellanicus; PG3 = H. macrotus, H. montanus; PG4 = Tadarida brasiliensis). The values of eleven variables were obtained for each point (e.g., temperature, relative humidity, vegetation cover, productivity, elevation, and proximity to water). Using generalized linear mixed-effects models (GLMMs), we analyzed how climatic and environmental variables influenced the spatial activity of Patagonian bat phonic groups.Results: Our results showed that spatial activity of four phonic groups analyzed in summer is driven by environmental (vegetation cover, elevation and proximity to water) and climatic variables (temperature and relative humidity). Nevertheless, the spatial activity of each specific phonic group was mainly influenced by vegetation cover variables and by their preference for each ecoregion, reflecting the habitat structure in which they forage.Conclusions: The spatial activity of four phonic groups from Central Patagonia in summer is governed jointly by climatic and environmental variables, with vegetation structure being the dominant driver. In the context of climate change, habitat loss and reduced water availability (especially in arid and semi-arid environments) could impact the populations of Patagonian bats, considering the importance of these factors in influencing their spatial activity.